World supply potential of rubberwood - Simula M (In: Proceedings of the International Forum on Investment Opportunities in the Rubber Wood Industry, 20-22 September 1993, Kuala Lumpur, Malaysia,pp. 1-15., 1993)
In 1991, the total world rubber plantation area was 9 million hectares, mostly in Asia, with an average growing stock of 95 m3/ha. The annual production potential of Rubberwood is currently estimated at 39 million m3 of which 11 million m3 is suitable for saw and veneer logs. It is estimated that the potential production will grow up to 52 million m3 by 2010. At present about 8 million m3 of Rubberwood logs should be economically available. The most important factors limiting Rubberwood supply are inadequate infrastructure and the high smallholders' share of the total rubber area. Rubberwood supply can significantly improve the profitability of rubber plantations, of which 75;are managed by smallholders. Several policy issues have to be solved to accelerate Rubberwood utilisation, which is justified based on financial, economic, social and environmental criteria. Long-term sustainable wood supply has to be established to enable necessary investment decisions.
Keywords: Rubberwood